(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2021)
The article presents data on the study of lichen biota in the city of Beregovo (Zakarpattia region). Totaly, 84 species of lichens and 13 species of lichenicolous fungi were identified. Among them Bryostigma phaeophysciae, Epiphloea byssina, Heterocephalacria physciacearum, Laetisaria lichenicola, Lichenochora obscuroides, Stigmidium fuscatae, Xanthomendoza huculica are reported for the first time to the Zakarpattia region. Calogaya decipiens, Candelariella aurella, C. vitellina, Flavoplaca austrocitrina, and Xanthocarpia crenulatella were quite common on reinforced concrete structures in town. Circinaria contorta, Protoparmeliopsis muralis, Polyozosia dispersa, and Sarcogyne regularis grows on stone fences and house foundations. Botanical reserve “Ardov” is situated in the ourkirts of Beregovo town and represented by a pannonian oak forest with a few silicicolous outcrops. Acarospora fuscata, Circinaria caesiocinerea, Rhizocarpon distinctum, R. geographicum, Trapelia placodioides, Xanthoparmelia conspersa, X. pulla are dominated on the siliceous outcrops on Ardov Mt. Bactrospora dryina is a rare corticolous species which can be an indicator of virgin oak forest was found on Ardov Mt. Only eight terricolous species were found during this research. Among them, Catapyrenium squamulosum, Epiphloea byssina, Peltigera didactyla and Scytinium tenuissimum are rarely reported on soil of hills near a small lake. Cladonia cenotea, C. fimbriata, C. subcariosa, and C. rangiformis were found on the ground between the boulders only on Ardov Mt. Corticolous lichens within town represented by typical nitrophylous species.